Toefl in the career of profesorado en idioma inglés - Sánchez Gómez, Sandra Dalila; Arías López, José Mauricio; Salazar Murcia, Pedro Antonio; Salazar Mucia, Pedro Antonio (San Salvador : Universidad de El Salvador, 2003)
This Argumentative essay is based on the new modality (TOEFL test) implemented by MINED in the career of “Profesorado en Idioma Inglés,” and on the changes this new implementation has caused in the curriculum, and requirements of admission of this career. The TOEFL, which is a test that measures the proficiency level of the English Language, was approved and implemented in this year (2003), and according to “El Instructivo Para El Funcionamiento de las Carreras de Profesorado,” the students of “Profesorado en Idioma Inglés” in process of graduation, for the year 2005, will have to submit to the TOEFL. The main objective of this modality and changes in the career of “Profesorado en Idioma Inglès,” in accordance with MINED, is to improve the quality of the teachers in the English area. The purpose of this research work is to show the reader that the objective that MINED chases is far from being achieved, since, besides the changes in this career, MINED should have done changes in the curriculums of Basic and Middle Education in order to make this plan functional and achieve the objective of improving the quality of the future teacher in the English area.
Tesis (Licenciatura en idioma ingles ópción enseñanza) -- Universidad de El Salvador
Bibliography : h 29-30
Keywords: Inglés -- Enseñanza; Estudiantes Universitarios -- Evaluación; Mediciones y pruevas educativas